On the relationship between corticomuscular (EEG-EMG) phase coupling and muscular fatigue - Joseph, Jeff Varkey Joshy (Division of Biomedical Engineering, 2015)
Contradictory results have been shown in studies measuring the effect of muscle fatigue on the level of synchrony between the oscillatory, cortical and muscular electrical activities (also known as corticomuscular coupling). In every study, the standard method (coherence) used to measure the level of synchrony takes into account both the amplitude and phase of the two signals. However, the use of the phase lock value (PLV) has been over looked as a method for determining the level of synchrony. While the PLV is modulated purely by the phase between the two signals, it is unaffected by any amplitude variation. This study aims to determine whether amplitude variations in electroencephalography (EEG) and electromyography (EMG) could have caused the contradictory results when comparing pre-,during and post-fatigue measures of corticomuscular coupling, which consequently affected the conclusions drawn regarding the monitoring of fatigue by the central nervous system. A determination will be made regarding the contradictions by directly comparing the two methods (coherence and PLV) on the same dataset of simultaneously measured EEG and EMG signals throughout an isometric pre-, during and post-fatigue task.